Assessment of the effects of the RSBS Closure to the work performance of the 3rd Infantry Division, Philippine Army morale, work attitude and issues and concern - Bilan, Miguel Jr
This study seeks to determine the true sentiments, views, opinions an perceptions of the military personnel on the closure of the Retirement and Separation Benefit system (RSBS) as well as the closure's effect on their work performance. This study would provide worthwhile findings that would serve as reference for future decision makings. It is assumed therefore, that the result of this study could aid decision makers to formulate programs that would truly answer concerns that affect the performance of the military servicemen. Sixty-one military servicemen were chosen from two separate camp assignments as respondents to this research project. Their awareness, sentiments views and suggestions were given sufficient consideration as well as their perception as to the effect of the closure of the supposedly their major source of security after retirement on their morale, attitude andwork performance. By seeking out the true sentiments of the people concerned and will be affected by the unfortunate closure of the RSBS, future decision-making maybe guided and potential problem maybe acted proactively. Undermining these sentiments could result to a disloyalty and perhaps low performance. The awareness and full understanding of theconcerned on the matter of dealing with their after-service benefits must be observed by any organization to maintain smooth working relationships and to boost the morale of its workers. As far as the survey results, it seems that this matter is not given ample discussion by the management of RSBS to be understood by the majority of the military personnel. Inretrospect, military men are one of the most highly respected being known for their loyalty and work dedication giving them less time to entertain other matters especially whenever they are on the job. Majority of the respondents believed that if only their contributions were managed well, RSBS could have survived and delivered what it ought to provide itsretired members. Unfortunately though, majority of the members would just contend with receiving the refund of their contributions. The closure of RSBS and the vast uncertainties of the future of the investments or contributions of its members have certainly affected the morale of the military men but they remained willing to fulfill their commitment to thenation and its people. The study recommends that if ever the military organization would still be willing to establish a new pension plan for its personnel, it should be managed by capable individuals and should establish a clear guidelines and policies to ensure that it will never end in bankruptcy as what the former RSBS has suffered.